Effect of Blood Component Coatings of Enosseal Implants on Proliferation and Synthetic Activity of Human Osteoblasts and Cytokine Production of Peripheral Blood Mononuclear Cells. (29th August 2016) - Himmlova, Lucie; Kubies, Dana; Hulejova, Hana; Bartova, Jirina; Riedel, Tomas; Stikarova, Jana; Suttnar, Jiri; Pesakova, Vlasta
Abstract : The study monitored in vitro early response of connective tissue cells and immunocompetent cells to enosseal implant materials coated by different blood components (serum, activated plasma, and plasma/platelets) to evaluate human osteoblast proliferation and synthetic activity and inflammatory response presented as a cytokine profile of peripheral blood mononuclear cells (PBMCs) under conditions imitating the situation upon implantation. The cells were cultivated on coated Ti-plasma-sprayed (Ti-PS), Ti-etched (Ti-Etch), Ti-hydroxyapatite (Ti-HA), and ZrO2 surfaces. The plasma/platelets coating supported osteoblast proliferation only on osteoconductive Ti-HA and Ti-Etch whereas activated plasma enhanced proliferation on all surfaces. Differentiation (BAP) and IL-8 production remained unchanged or decreased irrespective of the coating and surface; only the serum and plasma/platelets-coated ZrO2 exhibited higher BAP and IL-8 expression. RANKL production increased on serum and activated plasma coatings. PBMCs produced especially cytokines playing role in inflammatory phase of wound healing, that is, IL-6, GRO- α, GRO, ENA-78, IL-8, GM-CSF, EGF, and MCP-1. Cytokine profiles were comparable for all tested surfaces; only ENA-78, IL-8, GM-CSF, and MCP-1 expression depended on materials and coatings. The activated plasma coating led to uniformed surfaces and represented a favorable treatment especially for bioinert Ti-PS and ZrO2 whereas all coatings had no distinctive effect on bioactive Ti-HA and Ti-Etch.